The Pengaruh Quality Of Work Life, Perceived Organizational Support, dan Organizational Culture terhadap Employee Performance Perawat di Rumah Sakit Umum Daerah Kabupaten Bengkayang - Livrika, Yulita; Santosa, Awan (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
Health service problems include suboptimal service quality, complicated bureaucratic procedures and limited budgets for patients. This study aims to analyze the effect of Quality of Work Life, Perceived Organizational Support, and Organizational Culture on Employee Performance at the Bengkayang Regency Hospital. This study uses a type of causal quantitative research survey method and purposive sampling technique. The results of this study indicate that Quality of Work Life has no positive and significant effect on Employee Performance, Perceived Organizational Support has a positive and significant effect on Employee Performance, and Organizational Culture has a positive and significant effect on Employee Performance.